2007
DOI: 10.1089/thy.2006.0303
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Mass Spectrometry Improves the Accuracy of Free Thyroxine Measurements During Pregnancy

Abstract: Objective-Pregnancy is a time of rapidly changing demands on the thyroid axis, and knowledge of thyroid hormone levels, especially during the first trimester, is important for ensuring maternal and fetal health. The thyroid hormone assays currently in use become more inaccurate at extremes of binding protein concentrations and when heterophilic antibodies are present. Pregnancy is characterized by both these conditions, making accurate determination of free thyroid hormone levels by conventional direct analog … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 49 publications
8
98
0
3
Order By: Relevance
“…The use of tandem mass spectrometry may improve the accuracy of FT4 measurements during pregnancy (25 ). This technique is resistant to potential interference from heterophile antibodies, which may affect measurements by immunoassay throughout pregnancy (26,27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of tandem mass spectrometry may improve the accuracy of FT4 measurements during pregnancy (25 ). This technique is resistant to potential interference from heterophile antibodies, which may affect measurements by immunoassay throughout pregnancy (26,27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the measurement of maternal FT 4 with the immunoassay techniques currently used presents some difficulties due to insufficient accuracy by virtue of the interference of pregnancy-modified plasma proteins. It has been recently shown that certain FT 4 immunoassays can be quite similar to tandem mass spectrometry, which in turn has proven to have a high correlation with equilibrium dialysis, which is the gold standard for measurement of FT 4 during pregnancy (75,76). The determination of total T 4 (TT 4 ) has also been proposed as an alternative method for evaluating thyroid function during pregnancy, as TT 4 measurements are performed by a more robust methodology than those used for FT 4 .…”
Section: Obstetric Complications Associated With Td "mentioning
confidence: 99%
“…Although FT 4 measurement during pregnancy has some technical problems and its concentrations are particularly low in the third trimester compared with the nonpregnant population, the combination of a robust screening parameter such as TSH, as the first line approach, complemented with FT 4 measured with a method showing a good correlation with equilibrium dialysis or tandem mass spectrometry, which could allow a realistic and reliable protocol for detecting TD early in pregnancy. In the near future, tandem mass spectrometry, which has shown a very good correlation with equilibrium dialysis during gestation (76), may be the technique to be used for such purposes. Another factor to consider during pregnancy is the observed inverse relationship between FT 4 and weight (127,128).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Measurement of fT4 in the dialysate or ultrafiltrate of serum samples using liquid chromatography/tandem mass spectrometry appears to be the most reliable method and when this is used, fT4 concentrations were shown to decrease gradually with advancing gestational age, particularly between the 1 st and 2 nd trimester. 12,13 This assay is relatively expensive and not universally available. Routine fT4 assays (and probably fT3 assays) frequently fail to meet performance standards in pregnant women, owing to increases in TBG and decreases in albumin concentrations that cause the immunoassay to be unreliable.…”
Section: Subjectsmentioning
confidence: 99%